FACTORS RELATIONSHIP ORAL HYGIENE AND THE INCIDENT OF RECURRENT APHTHOUS STOMATITIS IN THE WORKING AREA OF THE HEALTH CENTER - Apriyanti, Apriyanti (PT. Nursing Genius Care, 2024)
Background:Stomatitis is a common oral disease that affects chewing function. Oral hygiene, nutrition, and trauma are thought to be predisposing factors. This study aims to determine the relationship of oral hygiene, nutrition, and trauma to the incidence of stomatitis in the working area of the Ranomeeto Public Health Center, South Konawe Regency. Objective:To analyze the relationship of oral hygiene, nutrition, and trauma to the incidence of stomatitis. Methods:This was a quantitative study with a cross-sectional design involving 68 respondents selected by proportional random sampling. The study was conducted from July to August 2019. Data were collected using questionnaires and analyzed using the chi-square test. Results showed that oral hygiene (p = 0.007), nutrition (p = 0.000), and trauma (p = 0.000) have a significant relationship with the incidence of stomatitis. Oral hygiene had a moderate correlation (phi coefficient = 0.329), nutrition also had a moderate correlation (phi coefficient = 0.490), and trauma had a strong correlation (phi coefficient = 0.527). Conclusion: There is a significant relationship between oral hygiene, nutrition, trauma, and the incidence of stomatitis in the working area of the Ranomeeto Public Health Center, South Konawe Regency. Attention to oral hygiene, nutrition, and the prevention of trauma is important for effective prevention.